Synthesis and Cleavage of Enterovirus Polypeptides in Mammalian Cells - Kiehn, E. D. (1970)
Evidence is presented that the entire enterovirus ribonucleic acid genome is translated into a single giant polypeptide of well over 200,000 daltons molecular weight. This giant protein was detected repeatedly in coxsackievirus B1-infected cells, even in the absence of amino acid analogues. The enzymes which cleave this giant protein into smaller structural and enzymatic proteins accumulate with increasing time after infection. It appears that they are either virus-coded proteolytic enzymes or else host enzymes which are activated or released from an intracellular site as a result of virus infection. These cleavage enzymes do not cause grossly apparent cleavage of host-cell proteins.